Generation and resource potential of abiogenic alkane gas under organic–inorganic interactions in petroliferous basins - Quanyou Liu; Xiaoqi Wu; Dongya Zhu; Qingqiang Meng; Huiyuan Xu; Weilong Peng; Xiaowei Huang; Jiayi Liu (Journal of Natural Gas Geoscience, 2021)
The generation mechanism of abiogenic alkane gas and whether the gas has industrial values are the focus of international attention. CH4 generated by Fischer–Tropsch synthesis is an important constitutent of abiogenic alkane gas. The study on the components, isotopic compositions, and crust-mantle mixing model indicates that, the alkane gas from the Qingshen gas field in the Songliao Basin is contributed by abiogenic alkane gas from Fischer–Tropsch synthesis, besides the mantle-derived abiogenic alkane gas. The authors have selected the endmembers of typical biogenic and abiogenic gases and conducted mixed source calculation. The abiogenic alkane gas accounts for over 60 × 109 m3 in the proven reserves of the gas field, in which the amount of CH4 generated by Fischer–Tropsch synthesis exceeds 9.6 × 109 m3. The calculation results indicate that, abiogenic alkane gas under organic–inorganic interactions can form commercial accumulations. Since typical biogenic gas is predominant in conventional gas pools, and high- to over-mature coal-derived gas displays a certain similarity with abiogenic alkane gas, the typical characteristics of abiogenic gas is concealed. Therefore, abiogenic alkane gas generated by organic–inorganic interactions may exist widely in petroliferous basins, and its contribution to gas pools may be underestimated previously.